Preterm Labor and Maternal Hypoxia in Patients With Community-Acquired Pneumonia - Maurizio L. Maccato; Phillip Pinell; Mark G. Martens; Sebastian Faro (Hindawi Limited, 1996)
Objective: We sought to determine if preterm labor is associated with the degree of maternal hypoxia in pregnant women with community-acquired pneumonia but no other maternal diseases.